“If I can accept my queerness, I can accept my body as it is”: Understanding weight-related perspectives and stigma from sexual minority women - Fowler, Lauren A.; Wang, Yilin; Wall, Catherine; Velkovich, Allyson; Harrop, Erin N.; Vázquez, Melissa M.; Mensah, Janis; Flentje, Annesa; Mann, Emily S. (Frontiers in Psychiatry, 2025)
IntroductionSociocultural norms that conflate thinness with health and morality contribute to widespread weight stigma, with well-documented consequences for physical and mental health. Sexual minority women (SMW), particularly those living in larger bodies, may be especially affected due to the intersection of heterosexism, sexism, and weight stigma across their lives.MethodsThis qualitative study utilized life history-informed semi-structured interviews with 24 cisgender SMW, ages 22–46, to explore how they experience sociocultural messages about weight, body size, and health over time, and how these experiences intersect with other aspects of structural marginalization. Interviews were audio recorded and transcripts were coded using a reflexive thematic analysis approach.ResultsThree overarching contexts were identified in which weight stigma is reinforced and resisted (1): dominant cultural norms—across media, healthcare, and public spaces—that moralized weight and pathologized larger bodies (2); families of origin, where intergenerational dieting, food restriction, and body surveillance reinforced weight bias beginning in childhood; and (3) queer communities, which sometimes fostered acceptance but also reproduced exclusionary body norms shaped by gender presentation, race, and size. Across settings, participants described the cumulative and compounding effects of stigma on mental health, including disordered eating. Their experiences also highlighted the complex role of sexual identity and queer community in shaping body-related experiences, which were affirming, marginalizing, and both simultaneously.DiscussionOur findings underscore the importance of applying intersectional and life-course frameworks and call for systemic changes in public health to shift from weight-centric approaches toward affirming, weight-inclusive paradigms that address interlocking systems of oppression.